Disease Pattern and Outcome of Neonates at Special Newborn Care Unit (SNCU) of Pokhara Academy of Health Science (PAHS), Nepal - Banstola, Ramchandra; Shrestha, Shreekrishna; Ghimire, JJ; Gurung, R; Sigdel, YR (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: This study was conducted to identify the causes and the outcome of neonates admitted to SNCU of Western Regional Hospital. Methods: A retrospective study was conducted at SNCU of western Regional Hospital, a referral tertiary centre of Western Region of Nepal from March 2016 to March 2017. Results: Total of 1144 neonates were admitted in NICU comprised of 562 (49.12.%) neonatal sepsis, 164 (14.33%) neonatal hyperbilirubinemia, 120 (10.48%) birth asphyxia, 109 (9.52%) premature, 92 (8.04%) Meconium Aspiration Syndrome, 96 (8.39%) Congenital anomalies and 14 (1.22%) necrotizing enterocolitis. Out of neonatal sepsis, 20.62% were early onset and 28.49% late onset conditions. Among Birth asphyxia, 102 (85.00%) were of HIE I& II and 18 (15%) of HIE III. Overall mortality observed was 3.32%. Those who required mechanical ventilation had higher mortality (87.50%) than the cases that were kept for CPAP (14.81%). Conclusions: Neonatal Sepsis, birth asphyxia, prematurity and Neonatal hyperbilirubinemia were major causes for admission in SNCU.